Penerapan Model Frayer Untuk Meningkatkan Kosakata Bahasa Arab Siswa - Siti Rofiqoh; Mabrurrosi Mabrurrosi (Paedagogos: Journal of Education and Learning, 2025)
Vocabulary learning is an important aspect of mastering Arabic at the elementary school level. However, in practice, students often experience difficulties in understanding and memorizing Arabic vocabulary due to the use of less varied teaching methods. This study aims to examine the implementation of the Frayer Model in improving students’ Arabic vocabulary at SD Bina Anak Sholeh (BAS) Latsari Tuban and to determine the improvement in students’ vocabulary mastery after the application of this model. This research employed a quantitative approach using Classroom Action Research (CAR), which was conducted in two cycles. The research subjects were students of SD Bina Anak Sholeh (BAS) Latsari Tuban. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive quantitative analysis. The results showed that the implementation of the Frayer Model effectively improved students’ Arabic vocabulary mastery. This improvement was indicated by an increase in the average scores and the percentage of students’ learning completeness from cycle I to cycle II and cycle III.